2016
DOI: 10.1111/hex.12520
|View full text |Cite
|
Sign up to set email alerts
|

Easy read and accessible information for people with intellectual disabilities: Is it worth it? A meta‐narrative literature review

Abstract: BackgroundThe proliferation of “accessible information” for people with intellectual disabilities in UK health care has accelerated in recent years, underpinned by policy guidance alongside the recent introduction of mandatory standards. However, questions have been raised as to the impact of such resources as a means of enhancing involvement in health care and addressing health inequalities.ObjectiveTo review and synthesize the evidence from different approaches used to evaluate the impact of accessible infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 64 publications
2
64
1
2
Order By: Relevance
“…Further, accessible communication depends on the individual; easy‐read information is not always accessible to all people with learning disabilities and it is important to take individual needs into account. Some easy‐read material may leave out important details in the quest for simplicity, such as contraindications or the patient's right to opt out of treatment (Chinn & Homeyard, ). Alternatives to easy‐read leaflets are visual or audio formats; however, some of our participants reported that they found it difficult to remember verbal information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, accessible communication depends on the individual; easy‐read information is not always accessible to all people with learning disabilities and it is important to take individual needs into account. Some easy‐read material may leave out important details in the quest for simplicity, such as contraindications or the patient's right to opt out of treatment (Chinn & Homeyard, ). Alternatives to easy‐read leaflets are visual or audio formats; however, some of our participants reported that they found it difficult to remember verbal information.…”
Section: Discussionmentioning
confidence: 99%
“…should be combined with verbal information in a consultation that is tailored to the person. Adapted health information has a better chance of making an impact when it is tailored to an individual's individual requirements (Chinn & Homeyard, ). Further, it is important that the resources should be co‐produced with people with learning disabilities who are more likely to have experienced the insufficiency of health information as described in this study and the wider literature (Ward & Townsley, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L'importance de donner de l'information sur les services a été relevée dans de nombreuses études (Chinn & Homeyard, 2017;King, Williams & Hahn-Goldberg, 2017;Mitchell & Sloper, 2002;Samuel, Hobden, Leroy & Lacey, 2012). Être informé correspond à un besoin identifié par les parents qui reçoivent des services pour leur enfant (Leblanc, Robert & Boyer, 2013).…”
Section: Le Besoin D'être Informé Sur Les Servicesunclassified
“…Whilst the importance for people with intellectual disability to have access to information is acknowledged in the research literature, its impact and usefulness are also questioned. Chinn and Homeyard’s () meta‐review refers to questions about its impact in meeting ‘personalized health information needs for people with intellectual disability’ (p. 1,189), a question that is also raised by Goodwin, Mason, Williams, and Townsley () regarding information about research. Likewise, Anderson et al () note that the production of easy‐to‐read information is not equalled by evidence that supports the effectiveness of its use.…”
Section: Introductionmentioning
confidence: 99%